Cell-to-cell interaction of Streptococcus sanguis and Propionibacterium acnes on saliva-coated hydroxyapatite. - Ciardi, J E (1987)
Cell-to-cell interaction (coaggregation) between Propionibacterium acnes PK93 and Streptococcus sanguis DL1 was measured on saliva-coated hydroxyapatite beads (SHA) at bacterial concentrations between 1.3 X 10(6) and 6.7 X 10(8) cells per ml. Four hundredfold more DL1 than PK93 cells adhered to the saliva-coated beads, and the adherence of S. sanguis was proportional to cell input. SHA precoated with 3 X 10(8) DL1 cells bound 75 to 80% of available PK93 cells at all input amounts tested, up to an input of 8 X 10(7) cells. Adherence of PK93 to DL1-coated SHA approached saturation at an input of approximately 10(9) PK93 cells, when 1.5 X 10(8) bound. The coaggregation on SHA occurred either in buffer or saliva and was inhibited by N-acetylgalactosamine and by lactose; the attachment of DL1 to SHA was not inhibited by these sugars. S. sanguis 34 and heat-treated DL1 cells, neither of which form coaggregates with PK93, attached to SHA, but such cells did not bind PK93 cells. The findings of this study indicate that bacteria unable to attach to saliva-coated hydroxyapatite can indeed adhere to such a surface by strong lectin-mediated cell-to-cell interactions with bacteria already attached to the surface.